Pengaruh Metode Sosiodrama Berbasis Audio Visual dalam Meningkatkan Motivasi Belajar dan Kemampuan Berbicara Siswa pada Mata Pelajaran Bahasa Indonesia Kelas V di SDN 4 Mamben Daya - Mashal Hadi; I Made Ardana; Ida Bagus Putu Arnyana (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to investigate the impact of the Audio-Visual-Based Sociodrama Method on enhancing learning motivation and Indonesian language skills among fifth-grade students at SDN 4 Mamben Daya. The research employed an experimental design with two groups: an experimental group using the Audio-Visual-Based Sociodrama method and a control group receiving conventional instruction. The assignment of experimental and control classes was done randomly. The study population consisted of all upper-grade students at SDN 4 Mamben Daya, totaling 101 students, from which 45 students were selected as the research sample. The results showed: First, there is a significant difference in learning motivation between students who participated in the Audio-Visual-Based Sociodrama Method and those who received conventional instruction. Second, there is a significant difference in Indonesian speaking skills between the two groups. Third, there is a significant difference in learning motivation and Indonesian speaking skills between students taught using the Audio-Visual-Based Sociodrama Method and those taught conventionally. In conclusion, the Audio-Visual-Based Sociodrama Method is effective in enhancing both learning motivation and Indonesian speaking skills among elementary school students.